Factors in the compulsory school environment that support male novice teachers - Jóhannesson, Ingólfur Ásgeir; Ottesen, Andri Rafn; Bjarnadóttir, Valgerður S. (Menntavísindasvið Háskóla Íslands, 2022)
This article reports from an interview study with seven male novice teachers who taught in six compulsory schools across Iceland. They taught mostly in Grades 4 to 10. The teachers were interviewed five times each during their first two years of teaching. The study was carried out to study gender-related issues in the induction of novice male teachers. This article focuses mainly on more general issues in their induction and has two goals: To cast light on what the novices saw as supportive and to propose pathways about the arrangement and expansion of novice induction in Iceland. We also asked which and what kind of factors in the school environment were supportive of male novice teachers The article is based on research about novice teachers, mentoring, and supervision. There is a general agreement in the literature that novices need careful induction into the job; also, that the induction needs to be formal but that informal factors can support formal mentoring and supervision. Several Icelandic studies have shown that formal induction and mentoring is seldom the case in Icelandic compulsory schools. Only two of the seven participants in this study had a formal mentor and, in these instances, they did not even meet as regularly as recommended. We knew this before we began analyzing our data, with the question about supporting factors in the school environment in mind. Our main findings include that our interviewees experienced a general welcoming attitude in the schools. They told us that they could ask anyone about what they needed, not only teachers but also school administrators, career counselors, and support staff. The most important support probably came from team teaching and other forms of cooperation with more experienced teachers. Although not all of our interviewees worked in a formal team-teaching setting, many of them knew of such settings within the same school, and they also pointed out that much support was provided in many varieties of informal cooperation between teachers during preparation ...